DE LA LIBERTATEA DE CONȘTIINȚĂ LA OBIECȚIA DE CONȘTIINȚĂ CA DREPT AL OMULUI. ASPECTE GENERALE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
From the Freedom of Conscience to the Conscientious Objection as a Human RightThe topic of freedom and of the conscientious objection has become nowadays a theme widely debated, both in the political area and in the religious one. On the scale of values and fundamental human rights the individual freedom certainly represents a unique social value, on which happiness and individual and collective wealth depends the most. Starting from The International Convention regarding the civil and political rights from 1966, according to which any human being has the right of freedom of thought, conscience and religion, the present article aims to undergo a short view in the issue of freedom of conscience an essential particularity of human nature, whose value must be recognized and guaranteed through specific legal means. In this context, the right to objection on the reason of conscience is made as being a right to freedom, as a moment of individual self-determination, configuration which supposes a mixture of different judicial decisions and figures, as we will see in the present article.